Guidelines for the application of 3D printing in the field of medical devices - ZHANG Wenfang; MOU Hongli; KUANG Xiaoying; LUO Huiyan; YANG Fan; HUANG Siyu (KeAi Communications Co., Ltd., 2021)
This paper briefly summarizes the regulatory laws and regulations for customized additive manufacturing medical devices in China, the United States, and Canada. There are still some differences in the clinical use and supervision of customized medical devices in different countries. The establishment of a scientific supervision model for customized medical devices can better promote its development. At the same time, in the process of supervision, it is necessary to conduct long-term observation of customized medical devices, assess their risks, and trace their sources. It is advisable to strengthen communication and cooperation between regulatory reviewers, technical employees, and medical staff to jointly guarantee the safety and effectiveness of products.